2009
DOI: 10.1097/sih.0b013e3181b3e4ab
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Training Improves Medical Students’ Learning Experiences When Performing Real Vaginal Deliveries

Abstract: Students who receive simulation training participate more actively in the clinical environment during the course of the clerkship. Student simulation training is beneficial to learn obstetric skills in a minimal risk environment, demonstrate competency with maneuvers, and translate this competence into increased clinical participation and confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 8 publications
1
60
0
3
Order By: Relevance
“…7,11,13,14,16,18,21,41 However studies reporting obstetric emergency training were the most frequently reported highlighting the need to practice often infrequent complex emergencies in a simulated setting. Training covered umbilical cord prolapsed, 42 vaginal breech delivery, 21 pre-eclampsia, 31,43 PPH, 15,28,44 shoulder dystocia, 20,24,27,30,45 and combinations of the above.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…7,11,13,14,16,18,21,41 However studies reporting obstetric emergency training were the most frequently reported highlighting the need to practice often infrequent complex emergencies in a simulated setting. Training covered umbilical cord prolapsed, 42 vaginal breech delivery, 21 pre-eclampsia, 31,43 PPH, 15,28,44 shoulder dystocia, 20,24,27,30,45 and combinations of the above.…”
Section: Introductionmentioning
confidence: 97%
“…2,[9][10][11][12][13][14][15][16] Obstetricians, residents and medical students studying obstetric skills. [17][18][19][20][21][22][23][24][25] Team based studies (including obstetricians, residents, midwives, medical students, nurse anaesthetists; nurse midwives; auxiliaries). [26][27][28][29][30][31][32][33][34][35] Curricula approach…”
Section: Introductionmentioning
confidence: 99%
“…In other medical educational settings, simulations have been used successfully both in education and in testing. Five LOE 1 300 -304 and 10 LOE 2 [305][306][307][308][309][310][311][312][313][314] studies showed the benefit of using simulations as an educational tool. One LOE 1 study 315 showed the benefit of using simulation as an evaluative tool.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…6,8,9 The resident, midwife, or attending physician who supervised the student completed the checklist as an evaluation of the student's performance. The evaluating preceptors were blinded to the stimulator type used by each student during their orientation training.…”
Section: Education Researchmentioning
confidence: 99%